2020
DOI: 10.1038/s41415-020-1448-3
|View full text |Cite
|
Sign up to set email alerts
|

General dental practice and improved oral health: is there a win-win for both the professional establishment and government?

Abstract: This paper provides a novel approach to monitoring oral health outcomes in general dental practice. The approach has the potential to impact on social inequalities in oral health. The approach allows general practitioners, who wish to deliver services to impact on community oral health, to do so without the burden of current disincentives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Furthermore, the monitoring of service delivery by LHBs has focused on equality for dental practitioners rather than equity for patients, however, the response to the Covid-19 crisis has made NHS contracts conditional on risk based continuing care [43]. Richards et al (2020) highlight the fact that contract monitoring has to date, penalised general dental practitioners who wish to operate equitable practice towards their patients [21]. The USWDI showed itself to be a good predictor of health and as such may be of value to service monitors to assess the overall outcome of services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the monitoring of service delivery by LHBs has focused on equality for dental practitioners rather than equity for patients, however, the response to the Covid-19 crisis has made NHS contracts conditional on risk based continuing care [43]. Richards et al (2020) highlight the fact that contract monitoring has to date, penalised general dental practitioners who wish to operate equitable practice towards their patients [21]. The USWDI showed itself to be a good predictor of health and as such may be of value to service monitors to assess the overall outcome of services.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it had been suggested that local health agencies should form partnerships with dental practitioners through service level agreements that foster equitable health outcomes. However, there were unintended consequences resulting from the contract of 2006, where lower socio-economic groups were no longer attractive patients for GDPs, making access for care difficult for this sub-group in the community [21]. During this period, the treatment demands from communities continued to satisfy the supply of care provided by GDPs, where GDPs were kept occupied through performing interventions that were not totally based on oral health needs.…”
Section: Introductionmentioning
confidence: 99%
“…Richards et al (2020) highlight the fact that contract monitoring has to date, penalised general dental practitioners who wish to operate equitable practice towards their patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it had been suggested that local health agencies should form partnerships with dental practitioners through service level agreements that foster equitable health outcomes. However, there were unintended consequences resulting from the contract of 2006 where lower socio-economic groups were no longer attractive patients for GDPs, making access for care di cult for this sub-group in the community [22]. During this period the treatment demands from communities continued to satisfy the supply of care provided by GDPs, where GDPs were kept occupied through performing interventions that were not totally based on oral health need.…”
Section: Introductionmentioning
confidence: 99%
“…The availability, accessibility and acceptability of care is paramount if the rhetorical promotion of ongoing care is to be manifested in reality. For over two decades access to dental services within the UK has been difficult, particularly for lower socioeconomic groups [42]. General dental practitioners and government continue to work towards a suitable and sustainable NHS Dental Contract that satisfies both parties [43,44].…”
Section: Introductionmentioning
confidence: 99%